Patency of endoscopic ultrasound-guided gastroenterostomy in the treatment of malignant gastric outlet obstruction - Kastelijn, Janine B.; Moons, Leon M.G.; Garcia-Alonso, Francisco J.; Pérez-Miranda, Manuel; Masaryk, Viliam; Will, Uwe; Tarantino, Ilaria; van Dullemen, Hendrik M.; Bijlsma, Rina; Poley, Jan-Werner; Schwartz, Matthijs P.; Vleggaar, Frank P. (Endoscopy International Open, 2020)
Background and study aims Endoscopic ultrasound-guided gastroenterostomy (EUS-GE) with a lumen-apposing metal stent (LAMS) is a novel, minimally invasive technique in the palliative treatment of malignant gastric outlet obstruction (GOO). Several studies have demonstrated feasibility and safety of EUS-GE, but evidence on long-term durability is limited. The aim of this study was to evaluate patency of EUS-GE in treatment of malignant GOO.Patients and Methods An international multicenter study was performed in seven centers in four European countries. Patients who underwent EUS-GE with a LAMS between March 2015 and March 2019 for palliative treatment of symptomatic malignant GOO were included retrospectively. Our main outcome was recurrent obstruction due to LAMS dysfunction; other outcomes of interest were technical success, clinical success, adverse events (AEs), and survival.Results A total of 45 patients (mean age 69.9 ± 12.3 years and 48.9 % male) were included. Median duration of follow-up was 59 days (interquartile range [IQR] 41–128). Recurrent obstruction occurred in two patients (6.1 %), after 33 and 283 days of follow-up. Technical success was achieved in 39 patients (86.7 %). Clinical success was achieved in 33 patients (73.3 %). AEs occurred in 12 patients (26.7 %), of which five were fatal. Median overall survival was 57 days (IQR 32–114).Conclusions EUS-GE showed a low rate of recurrent obstruction. The relatively high number of fatal AEs underscores the importance of careful implementation of EUS-GE in clinical practice.